Synonyms Analysis of Nakaha and Zawaja in the Al-Qur'an - Wardah Toyibah; Viqie Ixbal Maulana; Muhammad Fauzi (Journal of Arabic Language Studies and Teaching, 2022)
This article aims to determine the different meanings of the Arabic words Nakaha and Zawaja through the analysis of several interpretations. This research uses a library research method, and the objects are both of the words mentioned in the Quran. Documentation method as a data collection technique. To analyze the data using the analysis of Miles and Huberman. The results of this study are in surah al-Baqarah verse 221 and Ad-Dukhan verse 54; the words Nakaha and Zawaja have the same meaning, namely marriage/married, but they differ in the use of the object. In surah al-Baqarah verse 221 uses the word al-Musyrikaat, while in surah Ad-Dukhan verse 54 uses the word Huurin 'In. The words Nakaha and Zawaja can not only be fixed in one or two chapters of the Quran because each word has its meaning depending on the context of the sentence used in each surah.   تهدف هذه الدراسة إلى اكتشاف معنى نكح وزوج في القرآن الكريم من خلال آراء المفسرين التي أوردها في كتبهم. واعتمدت هذه الدراسة على المنهج التحليلي لميليس وحوبيرمان، وتم جمع البيانات بطريقة العثور على لفظ نكح وزوج في القرآن الكريم وفي كتب التفاسير.  ونتائج هذه الدراسة هي في سورة البقرة الآية 221 والدخان الآية 54 وكلمتا "نكح" و"زوج" لها نفس المعنى أي "متزوج" ولكنها تختلف في استعمال المفعول به. حيث في سورة البقرة آية 221 تستخدم لفظ "المشركات" بينما في سورة الدخان الآية 54 تستخدم "حور عين". في الواقع، لا يمكن تثبيت لفظي "نكح" و"زوج" فقط في سورة واحدة أو اثنتين، لأن لكل لفظ معنًى خاصا به وذلك بالاعتماد على سياق الكلام المستخدم في كل سورة.